2015
DOI: 10.1371/journal.pone.0123456
|View full text |Cite|
|
Sign up to set email alerts
|

Interactive and Independent Associations between the Socioeconomic and Objective Built Environment on the Neighbourhood Level and Individual Health: A Systematic Review of Multilevel Studies

Abstract: BackgroundThe research question how contextual factors of neighbourhood environments influence individual health has gained increasing attention in public health research. Both socioeconomic neighbourhood characteristics and factors of the built environment play an important role for health and health-related behaviours. However, their reciprocal relationships have not been systematically reviewed so far. This systematic review aims to identify studies applying a multilevel modelling approach which consider bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
88
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 79 publications
1
88
0
5
Order By: Relevance
“…Importantly, relevant literature has underscored the importance of considering multiple dimensions of neighborhood context (Schüle and Bolte, 2015)—including economic disadvantage, safety, violence, and social norms—on substance use (Jackson et al, 2014). Emerging literature has provided a basis for conceptualizing these multiple dimensions of neighborhood context as general versus outcome-specific risk factors (Capaldi et al, 2009; Duncan et al, 2006; Furr-Holden et al, 2015; Lee et al, 2012; Moffitt, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, relevant literature has underscored the importance of considering multiple dimensions of neighborhood context (Schüle and Bolte, 2015)—including economic disadvantage, safety, violence, and social norms—on substance use (Jackson et al, 2014). Emerging literature has provided a basis for conceptualizing these multiple dimensions of neighborhood context as general versus outcome-specific risk factors (Capaldi et al, 2009; Duncan et al, 2006; Furr-Holden et al, 2015; Lee et al, 2012; Moffitt, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a simultaneous consideration of neighbourhood SEP and built environmental factors in order to disentangle their independent effects is still lacking for this age group (Schüle and Bolte, 2015). Studies differed also widely concerning their adjustment variables which were considered in multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…These components include the prevalence of healthy behaviors, neighborhood safety, access to healthy food, and a place to exercise. 4,6,20,3538 However, to our knowledge, this is the first study to establish a relation between a summary measure of population well-being and life expectancy in a national sample of communities. We also found that all six components of this summary measure—physical health, emotional health, life evaluation, healthy behaviors, basic access, and work environment—were significantly associated with life expectancy.…”
Section: Discussionmentioning
confidence: 87%